2012
DOI: 10.1002/ardp.201200038
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Based Design, Synthesis, and Pharmacological Evaluation of 3‐Methoxyquinoxalin‐2‐carboxamides as Structurally Novel Serotonin Type‐3 Receptor Antagonists

Abstract: Employing a ligand-based approach, 3-methoxyquinoxalin-2-carboxamides were designed as serotonin type-3 (5-HT(3) ) receptor antagonists and synthesized from the starting material o-phenylenediamine in a sequence of reactions. The structures of the synthesized compounds were confirmed by spectral data. These carboxamides were investigated for their 5-HT(3) receptor antagonisms in longitudinal muscle myenteric plexus preparations from guinea-pig ileum against a standard 5-HT(3) agonist, 2-methy-5-HT, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The proposed pharmacophoric elements (Figure ) that are necessary for 5‐HT 3 receptor antagonistic activity are an aromatic moiety, a basic moiety, and an intervening hydrogen bond acceptor moiety arranged at specific distances . Our earlier studies have indicated that nitrogen containing fused six‐membered aromatic ring (aromatic moiety) may constitute a suitable template in the design of novel 5‐HT 3 receptor antagonists . Previously, we had synthesized and screened few compounds based on the above pharmacophoric pattern , and the results were encouraging enough to prompt us for further synthesizing some closely related compounds with a similar approach.…”
Section: Physical Constants Of Synthesized Compounds 8a‐8omentioning
confidence: 99%
“…The proposed pharmacophoric elements (Figure ) that are necessary for 5‐HT 3 receptor antagonistic activity are an aromatic moiety, a basic moiety, and an intervening hydrogen bond acceptor moiety arranged at specific distances . Our earlier studies have indicated that nitrogen containing fused six‐membered aromatic ring (aromatic moiety) may constitute a suitable template in the design of novel 5‐HT 3 receptor antagonists . Previously, we had synthesized and screened few compounds based on the above pharmacophoric pattern , and the results were encouraging enough to prompt us for further synthesizing some closely related compounds with a similar approach.…”
Section: Physical Constants Of Synthesized Compounds 8a‐8omentioning
confidence: 99%
“…) proposed for the interaction of 5‐HT 3 receptor antagonists with the 5‐HT 3 receptor‐binding site: consist of a heteroaromatic core, a hydrogen‐bond acceptor moiety, and a basic nitrogen located at a specific distance . In recent years, we have been engaged in the preparation and screening of compounds based on the above pharmacophoric pattern and our earlier studies have indicated that nitrogen‐containing fused aromatic rings (heteroaromatic core) may serve as a suitable starting point for the design of novel 5‐HT 3 receptor antagonists . In addition, compounds based on the indolyl aromatic core were reported as being potential 5‐HT 3 receptor antagonists .…”
Section: Introductionmentioning
confidence: 99%
“…Given all of these factors, a series of N-substituted-3-methoxyquinoxalin-2-carboxamides as 5-HT 3 receptor antagonists were designed using the ligand-based approach [34] and were synthesized from the starting material, o-phenylenediamine, in the sequence of reactions depicted in scheme 1 (supplementary data). The targeted new chemical entities were preliminarily screened for their antidepressant potential using FST.…”
Section: Introductionmentioning
confidence: 99%